Menjaga Kualitas Pendidikan Di SMKN 1 Kota Serang Melalui Implementasi Manajemen Peserta Didik Yang Efektif - Oktavia Theresia Ompu Sunggu; Adellia Nur Azzani; Rizki Sudrajat (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This article discusses efforts to maintain the quality of education at SMK Negeri 1 Kota Serang through the implementation of effective student management. Effective student management is needed to create an optimal learning environment and improve student learning outcomes. The research method we use is a descriptive qualitative approach with the results of the data referring to literature studies on the internet. This article also discusses strategies for implementing effective student management at SMK Negeri 1 Kota Serang, including teacher competency training and development, parental involvement, application of educational technology, and collaboration with relevant stakeholders. The results of our research are that through the implementation of effective student management, it is hoped that SMK Negeri 1 Kota Serang can maintain and improve the quality of education, and produce graduates who are competent and ready to face the challenges of the world of work